Pesan Dakwah Akhlak dalam Animasi Serial Nusa dan Rara Pada Episode Toleransi di Media Youtube; Analisa Simiotik Roland Barthes - Defa Ristianto; Amalia Rosyadi Putri; Tenika illananingtyas (Institut Agama Islam Tribakti (IAIT) Kediri, 2020)
Nussa animation is an animation which is categorized as a medium for preaching. Because the messages conveyed were thick with Islamic teachings. However, not all viewers can understand what messages are contained in the animation. Due to this reason, the study aims to determine the messages of moral da'wah that can be seen directly or indirectly with Ronald Barthes' semiotic theory. The method used in this research is qualitative analysis, with data in the form of documents. Data collection using observation and documentation. The theory that is used as the basis is Roland Barthes' semiotic theory which focuses on denotative and connotative meanings. The results of the study are the denotative meaning of dakwah morals, (1) Have an attitude of help. (2) Always say thank you for a help. (3) Always have a sincere nature when helping. (4) Doing rejection well. (5) Providing opportunities for children to do good (6) giving love to children. (7) always say